Towards the Latin American SME of the future: Technological Dynamism and Social Inclusion (Mayéutica Revista Científica de Humanidades y Artes, 2017)
The information revolution and globalization are redefining the spectrum of development opportunities for countries and for SMEs. This article discusses seven main changes providing advantages: market segmentation in multiple small niches; the outsourcing practices of global corporations, network organizations; clusters of small firms; “glocalization”; the coexistence de advanced and traditional technologies, the new conditions of access to markets in small quantities and the environmental problems as criteria for innovation. This new context opens a possible vision for the development of Latin America focused on the "technologization" of natural resources and in the processing industries (since the Asians have specialized in fabrication). It would be accompanied by the development of multiple local businesses to generate wealth in every corner of the territory. However, the traditional SME support has to take into account the emergence of SKIEs (small knowledge intensive enterprises) whose growing importance as providers of services to the rest of the production system should be taken into account inthe policies of development and support. Thus, it is necessary to understand their peculiarities and differences from traditional SMEs in order to design policies appropriate for each type. The article illustrates how taking into account technological changes and how they turn opportunities for development into a moving targetis essential for successful policymaking.
Keywords: Pymes; technology; social inclusion